Conflict management and performance outcomes - Posthuma, Richard A (The International journal of conflict management, 2011)
Purpose - This introduction aims to summarize five studies included in this themed issue that focus on conflict management and performance outcomes. These studies highlight how conflict management research can help organizations perform more effectively.Design methodology approach - The five selected studies were combined into this single issue so that readers can compare and contrast scholarships from many countries and cultures, including Brazil, Canada, Indonesia, The Netherlands, Norway, and Taiwan to see how conflict management research relates to actual performance outcomes around the world.Findings - These studies show that negotiations conducted by two-person dyads resulted in higher outcomes when compared to negotiations conducted by multi-person groups. In addition, when negotiators consider more than one issue at a time and use a constructive problem solving approach, they can reach better outcomes. In addition, higher self-efficacy of the negotiator can increase objective negotiation outcomes, but only to a point beyond which more self-efficacy can have a negative effect. One dimension of employee work performance, innovation, is shown to have several interesting relationships with other variables. Two studies found that innovative work behaviors had a positive relationship to workplace conflict. One study showed that task conflict seemed to relate to increased innovative work behaviors. Another study found a positive relationship between a broader measure of innovative work behaviors and conflicted with workers. The positive relationship between task conflict and innovative behaviors seemed to increase when there was more support for innovation. In addition, the positive relationship between innovative behavior and conflict with coworkers seem to decrease when there was more distributive justice in workplace rewards. These studies also showed significant relationships between conflict management and subjective outcomes, such as subjective perceptions of negotiations, job satisfaction, turnover intentions, and relationships between coworkers.Research limitations implications - These studies outline ways for organizations to design conflict management principles both to increase the objective outcomes of negotiations and to induce their employees to be more innovative at work.Originality value - All five studies used original data not reported elsewhere and gathered in various countries that have not been reported in prior studies.